Structure-Guided Development of Mycobacterial Thymidine Monophosphate Kinase (MtbTMPK) Inhibitors: Unlocking New Frontiers in Tuberculosis Research - , Suvaiv; Singh, Kuldeep; Hasan, Syed Misbahul; Kushwaha, Shom Prakash; Zaidi, Syed Mehdi Hasan; Kumar, Arun; Shahanawaz, Mo. (Current Topics in Medicinal Chemistry, 2025)
Researchers are actively engaged in developing new antitubercular drugs targeting the enzyme Mycobacterial Thymidine Monophosphate Kinase (MtbTMPK). This newer target has specificity and selectivity over other thymidylate kinases and especially differs from human thymidylate kinase (hTMPK). Over the last two decades, various potent MtbTMPK inhibitors comprised of both nucleoside and non-nucleoside structures have been developed. Mostly, nucleoside inhibitors have encountered substantial challenges, primarily related to poor solubility and permeability, which often render them inactive in whole-cell antitubercular assays. Consequently, the focus has shifted towards identifying potent non-nucleoside inhibitors that demonstrate activity in whole-cell assays. Researchers have employed structure-based modifications and leveraged insights from co-crystal structures of <span class=
Keywords: Tuberculosis (TB)